Dynamics of forest net primary productivity based on tree ring reconstruction in the Tianshan Mountains. (February 2023) - Wang, Ting; Bao, Anming; Xu, Wenqiang; Zheng, Guoxiong; Nzabarinda, Vincent; Yu, Tao; Huang, Xiaoran; Long, Gang; Naibi, Sulei
Graphical abstract: Highlights: Tree ring is an ideal proxy for forest productivity. New sampling method was developed in order to estimate forest productivity using tree rings. Chronologies can be used to reconstruct forest productivity on long time scales. Abstract: The lack of long-term high-resolution data makes it difficult to determine historical and future trends in net primary productivity (NPP). This study used tree rings as a proxy to investigate the dynamics of NPP in Tianshan forests where coniferous forests are the major species and the other species are deficient. All trees and some tree cores from five sample plots in different geographic locations in the western Tianshan Mountains were selected to reconstruct forest NPP data from 1950 to 2020. Multiple historical events that resulted in large-scale terrestrial carbon fluxes were identified and the existence of 28a and 17a time-scale cycles of historical forest NPP was observed. We discovered that the reconstructed forest NPP in the western Tianshan Mountains did not significantly correlate with satellite-based products (e.g., MODIS NPP, solar-induced chlorophyll fluorescence data). This result was attributed to the lag of forest growth for climate, the accuracy of the satellite-based products and statistical errors due to the short overlap time. We analysed the uncertainties in reconstructing historical forest NPP using tree ring widths and proposed corresponding solutions. We concluded that the reconstructed data remain the ideal proxy for regions lacking long-term empirical data and exhibit a high degree of confidence for expressing trends in forest productivity change over long time series.